Response of the banana passion fruit (passiflora tripartita var. mollissima) to different levels of nitrogen, potassium and magnesium (2013)
In order to observe the effects of N, K, and Mg on dry mass (DM) allocation, canopy growth and nutritional deficiency symptom expression of the banana passion fruit (Passiflora tripartita var. mollissima), three levels of fertilization were evaluated: none (0), low (1) and high (2) of each element, and compared to complete fertilization (control), arranged in a randomized complete block design. Banana passion fruit plants were transplanted to plastic pots, containing a substrate of quartz sand, with irrigation twice a week and fertigation once a week. The evaluated variables were total dry weight (TDW), percentage of dry mass allocation, leaf area (LA), number of leaves (NL), specific leaf area (SLA) and leaf area ratio (LAR). In addition, a photographic record was taken to recognize the symptomatology in the leaves. The absence of N, K and Mg affected the accumulation of DM, whereas the high nutrient level allowed for the greatest gain in DM only with N, while with K and Mg, it was reduced, indicating that these doses may be too excessive. The distribution pattern of DM with the N treatments corresponded to the model proposed by Thornley, accumulating more DM in the root. With the K and Mg levels, the distribution pattern was similar with the absence of these nutrients causing higher DM accumulation in the above-ground plant parts. The leaf variables NL and LA were reduced with all three elements at the zero nutrient level, whereas the high indices of SLA and LAR revealed a low gain of DM. Deprivation of each nutrient showed characteristic symptoms on the leaves, mainly chlorosis with different patterns, necrosis and reduced LA.